Prenatal restraint stress decreases the expression of Alpha-7 Nicotinic receptor in the brain of adult rat offspring - Baier, Carlos Javier (2015)
Prenatal stress (PS) strongly impacts fetal brain development and function in adulthood. In normal aging and Alzheimer's disease, there is hypothalamic–pituitary–adrenal axis dysfunction and loss of cholinergic neurons and neuronal nicotinic acetylcholine receptors (nAChRs). This study investigated whether prenatal restraint stress affects nAChR expression in the brain of adult offspring. For PS, pregnant dams were placed in a plastic restrainer for 45 min, three times daily during the last week of pregnancy; controls were undisturbed. Male offspring were analyzed at postnatal day (PND) 60 (n = 4 rats per group). Western blot (WB) and fluorescence microscopy showed that PS decreased α7-AChR subunit expression (∼50%) in the frontal cortex in the adult offspring. PS decreased significantly the number of α7-AChR-expressing cells in the medial prefrontal cortex (by ∼25%) and in the sensory-motor cortex (by ∼20%) without affecting the total cell number in those areas. No alterations were found in the hippocampus by quantitative polymerase chain reaction (qPCR), or WB analysis, but a detailed fluorescence microscopy analysis showed that PS affected α7-AChR mainly in the CA3 and dentate gyrus subfields: PS decreased α7-AChR subunit expression by ∼25 and ∼30%, respectively. Importantly, PS decreased the number of α7-AChR-expressing cells and the total cell number (by ∼15 and 20%, respectively) in the dentate gyrus. PS differently affected α4-AChR: PS impaired its mRNA expression in the frontal cortex (by ∼50%), without affecting protein levels. These results demonstrate that disturbances during gestation produce long-term alterations in the expression pattern of α7-AChR in rat brain.